1992
DOI: 10.1016/0266-7681(92)90020-3
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Analysis of a New Interlock Suture Technique for Flexor Tendon Repair

Abstract: Using a computerised tensometer, both the gap-producing and breaking forces of a new interlocking suture for flexor tendon repair were compared to the modified Kessler and the Strickland techniques. 30 porcine deep flexor tendons were used in each group and all repairs were performed with 3/0 polypropylene sutures. The interlock technique withstood gap-producing and breaking forces significantly better than the modified Kessler and Strickland techniques. Also, the gap-producing force was closer to the breaking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 4 publications
2
31
0
Order By: Relevance
“…Wade et al 32 and Cieslik et al, 33 using stainless steel sutures, reported in vitro ultimate failure strengths of up to approximately 80 N; these studies suggest that stainless steel sutures have higher resistive loads to failure than conventional suture techniques. 13,34,35 Urbaniak et al 27 observed that stainless steel suture was stronger than polyester in a canine model until day 5, when all repairs failed by pulling out of the tendon substance owing to tenomalacia at the suture interface. The Teno Fix device was designed to use the superior material properties of stainless steel suture with an improved mechanism of knotless tendon anchoring.…”
Section: Discussionmentioning
confidence: 98%
“…Wade et al 32 and Cieslik et al, 33 using stainless steel sutures, reported in vitro ultimate failure strengths of up to approximately 80 N; these studies suggest that stainless steel sutures have higher resistive loads to failure than conventional suture techniques. 13,34,35 Urbaniak et al 27 observed that stainless steel suture was stronger than polyester in a canine model until day 5, when all repairs failed by pulling out of the tendon substance owing to tenomalacia at the suture interface. The Teno Fix device was designed to use the superior material properties of stainless steel suture with an improved mechanism of knotless tendon anchoring.…”
Section: Discussionmentioning
confidence: 98%
“…24 -27 Although modified forms of the Kessler technique are what many surgeons use, numerous other techniques have been described, many of which are aimed at providing a stronger repair. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] One of the common themes of these techniques is that the strength of each is related directly to the number of strands crossing the repair site, with 4-strand repairs being twice as strong as 2-strand repairs and 6-strand repairs being almost 3 times stronger. A number of 8-strand repair techniques also have been described.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have omitted additional epitendinous repair because this would have worked as bias by introducing other variables such as the epitendinous suture technique and suture material. For several common two-strand repairs (Bunnell, Kessler, Strickland, Tsuge), other authors [13,15,[28][29][30][31][32][33] have found a mean ultimate tensile strength below 35 N, even with epitendinous repair.…”
Section: Discussionmentioning
confidence: 99%